2017
DOI: 10.1371/journal.pone.0169221
|View full text |Cite
|
Sign up to set email alerts
|

Do Thai Physicians Recommend Seasonal Influenza Vaccines to Pregnant Women? A Cross-Sectional Survey of Physicians’ Perspectives and Practices in Thailand

Abstract: BackgroundPhysicians play a major role in influencing acceptance and uptake of vaccines. However, little is known about physicians’ perspectives on influenza vaccination of pregnant women in Thailand, for whom vaccine coverage is estimated at <1%.MethodIn 2013, a self-administered questionnaire on physicians’ perceptions, attitudes and practices related to influenza vaccination for pregnant women was distributed to 1,134 hospitals with an antenatal care clinic (ANC) in Thailand. At each hospital, one physician… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 24 publications
2
34
2
Order By: Relevance
“…Healthcare providers who are more knowledgeable [36, 37] and confident [38, 39] about the influenza vaccine are more likely to recommend vaccination and obtain high coverage among expecting mothers. In Singapore, qualitative studies have revealed limited influenza vaccine acceptance among healthcare professionals [40, 41].…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare providers who are more knowledgeable [36, 37] and confident [38, 39] about the influenza vaccine are more likely to recommend vaccination and obtain high coverage among expecting mothers. In Singapore, qualitative studies have revealed limited influenza vaccine acceptance among healthcare professionals [40, 41].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study conducted in Thailand, Praphasiri et al examined the association of characteristics of obstetricians and gynecologists and their reported practice in recommending influenza vaccine to pregnant women using a mail survey method . They reported that physicians were more likely to routinely recommend influenza vaccine to pregnant women when they were aware of the MOPH policy of influenza vaccination in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Years of practice, median (IQR) to pregnant women using a mail survey method. 52 They reported that physicians were more likely to routinely recommend influenza vaccine to pregnant women when they were aware of the MOPH policy of influenza vaccination in pregnancy. Consistently, all of our frequent recommenders stated they agreed with the MOPH policy.…”
Section: Con Clus Ionsmentioning
confidence: 99%
“…There is no doubt that some of adverse side-effects of a vaccine observed in the developing countries might be due to disguising of the clinical information by the patients. In Thailand, the focus is on promoting the availability of free influenza vaccination [6]; however, there is no additional concern regarding the way to control the safety use of the vaccine. In fact, the unreliability of the clinical history regarding vaccination is usually problematic.…”
Section: Discussionmentioning
confidence: 99%